PENGEMBANGAN MEDIA PEMBELAJARAN SCRATCH BERBASIS KEARIFAN LOKAL PADA MATERI HIMPUNAN - Thresia Yohana Sembiring; Agusmanto J.B Hutauruk; Yanty Marbun; Junaida Boang Manalu (Universitas Quality, 2022)
The purpose of the research is to develop a local wisdom-based scratch learning media on set material at SMP Negeri 1 Stabat for the 2022/2023 academic year. This type of research is Research and Development (R&D) development research. This research uses the ADDIE research design (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in this research were interviews, validation from experts including material experts, media experts, and mathematics learning experts, observation sheets, and documentation. The results of this development research are the implementation of learning using local wisdom-based scratch learning media in the good category and the feasibility of local wisdom-based scratch learning media in a very good category based on the validation results from experts, namely material experts obtaining a feasibility percentage of 86%, media experts obtaining a feasibility percentage of 85%, and Mathematics learning experts get a percentage of 89% eligibility. So it can be concluded that scratch learning media is based on local wisdom on practical set material to use. Thus, it can be concluded that the Development of Scratch Learning Media Based on Local Wisdom on Association Materials at SMP Negeri 1 Stabat for the 2022/2023 Academic Year is categorized as good learning implementation and the learning media developed is practical and feasible to use.